Enzymatic fructose removal from D‐psicose bioproduction model solution and the system modeling and simulation. Issue 5 (28th November 2017) - Li, Can; Zhang, Chengjia; Lin, Jianqun; Gao, Ling; Lin, Huibin; Lin, Jianqiang
Abstract: BACKGROUND: The rare sugar D‐psicose has important physiological functions, and has been used as an ingredient in foods and dietary supplements. It can be mass produced from D‐fructose in industry. However, separation of D‐psicose from D‐fructose is difficult. RESULTS: In this research, a reaction purification system consisting of two continuous stirred tank reactors (CSTR) containing immobilized glucose isomerase (GI) and glucose oxidase (GOD), respectively, for D‐fructose removal was constructed. Using this system D‐fructose was transformed into gluconic acid and separated from D‐psicose easily using anion exchange resin. Modeling and simulation was carried out for this system and the model was verified by experiments and used in process predictions. CONCLUSION: D‐Psicose can be efficiently purified using the proposed reaction purification system. The final purity of the D‐psicose is 91.2%, which meets the need for crystallization to obtain highly purified product. The mathematical model developed for this system can simulate and predict the process well, which is useful in process analysis, prediction, and optimization to save time and costs compared with laboratory experiments. © 2017 Society of Chemical Industry